Potential genetic modifiers of the cystic fibrosis intestinal inflammatory phenotype on mouse chromosomes 1, 9, and 10 - Norkina, Oxana (BioMed Central, 2005)
BACKGROUND: Although cystic fibrosis is caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, the severity of disease is highly variable indicating the influence of modifier genes. The intestines of Cftr deficient mice (CF mice: Cftr(tm1Unc)) are prone to obstruction by excessive mucus accumulation and are used as a model of meconium ileus and distal intestinal obstruction syndrome. This phenotype is strongly dependent on the genetic background of the mice. On the C57Bl/6 background, the majority of CF mice cannot survive on solid mouse chow, have inflammation of the small intestine, and are about 30% smaller than wild type littermates. In this work potential modifier loci of the CF intestinal phenotype were identified. RESULTS: CF mice on a mixed genetic background (95% C57Bl/6 and 5% 129Sv) were compared to CF mice congenic on the C57Bl/6 background for several parameters of the intestinal CF phenotype. CF mice on the mixed background exhibit significantly greater survival when fed dry mouse chow, have reduced intestinal inflammation as measured by quantitative RT-PCR for marker genes, have near normal body weight gain, and have reduced mucus accumulation in the intestinal crypts. There was an indication of a gender effect for body weight gain: males did not show a significant improvement at 4 weeks of age, but were of normal weight at 8 weeks, while females showed improvement at both 4 and 8 weeks. By a preliminary genome-wide PCR allele scanning, three regions were found to be potentially associated with the milder phenotype. One on chr.1, defined by marker D1Mit36, one on chr. 9 defined by marker D9Mit90, and one on chr. 10, defined by marker D10Mit14. CONCLUSION: Potential modifier regions were found that have a positive impact on the inflammatory phenotype of the CF mouse small intestine and animal survival. Identification of polymorphisms in specific genes in these regions should provide important new information about genetic modifiers of the CF intestinal phenotype.